A few FERPA training perspectives: Unexpected questions, Part 3. Issue 9 (8th October 2021) - Rainsberger, Richard
Abstract : It's always a good experience for me after I have conducted a Family Educational Rights and Privacy Act workshop to hear questions from the audience about what is affecting their professional lives in their specific offices. The alumni director and the computer center director from last month's column had FERPA questions relating to their own professional responsibilities. I had answered the alumni director's questions and one of the computer center director's questions. That one related to having a student's name on the subject line of an email. He hadn't expected my complex answer. So before we discussed the next question, he and I sat down.